TIGIW BUYÍMLARÍN KONSTRUKCIYALAW PÁNINDE OQÍW PROCESIN ShÓLKEMLESTIRIWDIŃ PEDAGOGIKALÍQ TEXNOLOGIYALARÍ - Berdimbetova, A.D. (SCIENCE and SOCIETY, 2025)
The article provides information on the effective organization of the educational process in garment construction lessons, the combination of pedagogical technologies with innovative approaches, and the application of modern teaching methods aimed at developing the knowledge, skills, and competencies of future teachers of technological education.